MTR recovery in brain lesions in the BECOME study of glatiramer acetate vs interferon β-1b. (30th August 2016) - Brown, Robert A.; Narayanan, Sridar; Stikov, Nikola; Cook, Stuart; Cadavid, Diego; Wolansky, Leo; Arnold, Douglas L.
Abstract : Objective: To compare magnetization transfer changes in new brain MRI lesions identified during monthly imaging in patients with multiple sclerosis (MS) randomized to treatment with 250 μg subcutaneous interferon-β-1b (IFN-β-1b) every other day or daily 20 mg glatiramer acetate (GA) in a post hoc study using data from the Betaseron Versus Copaxone for Relapsing Remitting or CIS Forms of MS Using Triple Dose Gad 3 T MRI (BECOME) trial. Methods: T1-weighted images acquired with and without fat saturation pulses in the BECOME study were evaluated and found to exhibit magnetization transfer ratio (MTR) effects, and were used to compute MTR images (FSMTR). Forty-three participants who had the required imaging and new lesions, from the 75 originally randomized into the BECOME study, were included in this post hoc analysis and evaluated longitudinally during treatment to determine FSMTRDrop, an experimental measure of the completeness of FSMTR recovery in new lesions. Two sets of new brain MRI lesions were defined, one based on the appearance of gadolinium contrast enhancement (Gd lesions) and the other based on FSMTR decreases (ΔFSMTR lesions). Results: A total of 887 Gd lesions were identified in 43 participants (19 GA, 24 IFN-β-1b) and 321 ΔFSMTR lesions in 32 participants (16 GA, 16 IFN-β-1b). Participants randomized to GA exhibited greater average postlesion FSMTR recovery than did those randomized to IFN-β-1b in both Gd ( p < 0.0001) and ΔFSMTR ( p < 0.0001) lesions. Conclusions: New brain lesions that developed during treatment with GA exhibited evidence of greater FSMTR recovery than during treatment with IFN-β-1b. Classification of evidence: This study provides Class III evidence that MTR recovery in patients with MS with new MRI brain lesions is greater with GA than with IFN-β-1b.